Ice sheet record of recent sea‐ice behavior and polynya variability in the Amundsen Sea, West Antarctica. Issue 1 (25th January 2013) - Criscitiello, Alison S.; Das, Sarah B.; Evans, Matthew J.; Frey, Karen E.; Conway, Howard; Joughin, Ian; Medley, Brooke; Steig, Eric J.
Abstract: [1] Our understanding of past sea‐ice variability is limited by the short length of satellite and instrumental records. Proxy records can extend these observations but require further development and validation. We compare methanesulfonic acid (MSA) and chloride (Cl – ) concentrations from a new firn core from coastal West Antarctica with satellite‐derived observations of regional sea‐ice concentration (SIC) in the Amundsen Sea (AS) to evaluate spatial and temporal correlations from 2002–2010. The high accumulation rate (~39 g∙cm –2 ∙yr –1 ) provides monthly resolved records of MSA and Cl –, allowing detailed investigation of how regional SIC is recorded in the ice‐sheet stratigraphy. Over the period 2002–2010 we find that the ice‐sheet chemistry is significantly correlated with SIC variability within the AS and Pine Island Bay polynyas. Based on this result, we evaluate the use of ice‐core chemistry as a proxy for interannual polynya variability in this region, one of the largest and most persistent polynya areas in Antarctica. MSA concentrations correlate strongly with summer SIC within the polynya regions, consistent with MSA at this site being derived from marine biological productivity during the spring and summer. Cl – concentrations correlate strongly with winter SIC within the polynyas as well as some regions outside the polynyas, consistent with Cl – at this site originating primarily from winter sea‐ice formation. Spatial correlations were generally insignificant outside of the polynya areas, with some notable exceptions. Ice‐core glaciochemical records from this dynamic region thus may provide a proxy for reconstructing AS and Pine Island Bay polynya variability prior to the satellite era. Key Points: MSA is primarily derived from polynya biological productivity in summer Cl‐ originates primarily from winter sea‐ice formation processes Ice‐core records may provide a proxy for reconstructing polynya variability